9-11 Year-Old Students' Perception of Violence Reflected in Their Drawings - Ozdemir, Melih Burak; Gürkan, Senem; Barut, Yashar (Khazar Univ, 2018)
Violence, which can be defined as any threat towards the physical and psychological integrity of a human being, can result in fear, anxiety and severe behavior problems on children, whether exposed or witnessed. In this study, it is planned to achieve children's perception of violence expressed by drawing and obtaining data in this way. In this study, the type of violence children portray in their drawings, how they determine to portray characteristics who perpetrate violence and are exposed to it as well as how is applied are analyzed. To measure how children perceive the violence, they were asked to draw a picture describing the ones who use violence and the ones who are exposed to violence. The pictures, drawn by children who participated in the study, were examined from a semantic perspective and content analysis method was adopted on the pictures. The research was conducted in Samsun province in the middle socio-economic level, with total of 53 students, 27 girls and 26 boys between the ages of 9-11 who were randomly selected representing two schools. Drawings were examined according to the issues they portrayed and then, semantic and content analysis was applied. In the children's drawings, it is shown that the violence of adults is reflected more. These findings indicate that child to child violence, domestic violence, war, adult to child violence, adults to animal violence and terrorism is portrayed respectively. Generally, males are portrayed in the drawings. Drawn illustrations show that children are aware of the growing violence in their environmental. Raising the children in nonviolent social environment seems important for their healthy development. We can say that drawing, which is a simple tool for exploring the children's inner world, can be used by all professionals responsible for children education.
Keywords: Violence; Drawing; Primary School; Terrorism; Education